Bactericidal effects of copper-polypyrrole composites modified with silver nanoparticles against Gram-positive and Gram-negative bacteria - Marucci Patricia L.; Sica Maria G.; Brugnoni Lorena I.; González María B. (Journal of the Serbian Chemical Society, 2023)
The aim of this research is to study the bactericidal effects of copper–polypyrrole (PPy) composites deposited onto 316L stainless steel (SS) modified with silver nanoparticles (Np). The antimicrobial properties were evaluated against twenty-four strains of Gram-positive and Gram-negative bacteria. Among the twenty-four strains studied, isolates included reference strains (Escherichia coli ATCC 25922, Escherichia coli 0157:H7 EDL 933, Staphylococcus aureus ATCC 25923 and Listeria monocytogenes ATCC 7644), as well as strains isolated from food and clinical samples. The antimicrobial activity of the composites demonstrated that all PPy-modified films had antibacterial properties. Notably, Cu-PPyAgNp500 exhibited the strongest inhibitory activity against both Gram-negative and Gram-positive bacteria. Surface modification of 316L SS with these films is a promising and viable alternative for the development of novel antibacterial composites that can inhibit the growth of a significant number of bacteria.